Effectiveness of Social Media-Based E-Learning In Enhancing Business Simulation Understanding: A Case of Edugate - Salima Fadhilatus Sholihah; Istyakara Muslichah; Dim Zarita Suryanugraha (Utan Kayu Publishing, 2026)
This study aims to analyze the effectiveness of social media as an instructional support tool in enhancing students’ understanding of a Business Simulation Game. The increasing integration of digital platforms in higher education has encouraged the use of social media as a supplementary learning medium. However, empirical evidence regarding its effectiveness in supporting simulation-based training remains limited. Therefore, this study examines whether social media-based learning contributed to improved learning outcomes and explores students’ learning experience of its implementation, grounded in the Technology Acceptance Model (TAM). The research employs a mixed-method approach involving 125 university students who participated in the competition. Quantitative data were collected through pre-test and post-test assessments as well as Likert-scale questionnaires, while qualitative data were obtained from open-ended responses. The data were analyzed using descriptive analysis, instrument validity and reliability testing, and N-Gain score analysis. The results indicate an increase in post-test scores compared to pre-test results, reflecting improved understanding after the implementation of social media-based instructional support. In addition, students expressed positive learning experience and perception in term of TAM. These findings confirms that social media can function effectively as a supplementary tool in Business Simulation Game competition.